BTS ARMY’s #BTSLOVEYOURSELF: A Worldwide K-Pop Fandom Participatory Culture on Twitter - Ayu Saraswati , Listya; ., Nurbaity (KnE Social Sciences, 2020)
Korean popular music (K-pop) fandom is under the spotlight as the K-pop industry has rapidly grown transnationally. Fandom practices across national borders in social media have emerged as fans support their idols by buying the records, continuously discussing their personal lives, attending live music concerts, and supporting social causes in the name of the idols. This paper investigates fandom participatory culture with regards to creating and supporting social activism message on social media. By collecting and analyzing a large volume of fandom activity data from Twitter, this study considers the prevalence of fandom participatory culture and considers the importance of K-pop’s transnationalism with regards to social activism on social media. By analyzing the Twitter data of ARMY on #BTSLOVEYOURSELF, we demonstrate that this participatory culture gives the fandom and their messages bigger effect on social media beyond the idol’s commercially-crafted public image. Keywords: K-pop fandom, participatory culture, social activism.